Improved on-chip self-triggered single-event transient measurement circuit design and applications. (April 2017) - Chen, Rongmei; Chen, Wei; Guo, Xiaoqiang; Shen, Chen; Zhang, Fengqi; Zheng, Lisang; Zhao, Wen; Ding, Lili; Luo, Yinhong; Guo, Hongxia; Wang, Yuanming; Liu, Yinong
Abstract: Single-event transient (SET) induced soft errors are becoming more and more a threat to the reliability of electronic systems in space. The SET pulse width is an important parameter characterizing the possibility of an SET being latched by a sequential element such as a flip-flop. This paper improves the widely used on-chip self-triggered SET measurement circuit by changing it from a single SET measurement module to a combination of two modules. One module is responsible for measuring narrow SET pulse widths while the other is responsible for measuring modest and wide SET pulse widths. In this way, the range of measurable SET pulse width is increased. Pulsed laser facility is used to simulate single-event transients induced by single-particles. Experimental results demonstrate that the minimum accurately measured SET pulse width is decreased from 166.5 ps to 33.3 ps after adopting the proposed design when compared with the original one. SET pulse width broadening effect was also observed using the measurement system. The broadening factor was measured to be 0.123–0.143 ps/inverter. Highlights: In nominal supply voltage, minimum accurately measured SET pulse width is significantly decreased. All benefits of the original design are kept without degradation. The design difficulty of the delay part in the original SET measurement circuit is immune in the proposed design. The advantage of the proposed design over the original one is clearly demonstrated with pulsed laser experiments.